HOW İS HEALTH INSURANCE ASSOCİATED WİTH OBESİTY İN WOMEN İN TURKEY? (Third Sector Social Economic Review, 2021)
Obesity poses a threat to economies since it has been associated with lower productivity of labor, an increase in non-communicable diseases such as diabetes and cardiovascular diseases and an increasing healthcare costs due to these diseases. Prevalence of obesity among women in Turkey has been higher than that for men and rising over time. Although health insurance protects against financial burden of diseases, it has been argued that it may increase the risk of obesity due to ex ante moral hazard which refers to the case that individuals may engage in riskier behaviors when they are insured. This paper aims to analyze the association between health insurance and obesity in women in Turkey by using micro level national data. Regression results show that having health insurance is associated with a higher likelihood of being obese by controlling for the socio-economic variables and a dummy variable for the study period.
Keywords: Obesity; Health Insurance; Women; Turkey